Effect of two hypoxic environment stimuli on erythropoietin and aerobic capacity - Xiao, G.; Huang, J.; Zhou, W.; Hu, Y. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The purpose of our study was to investigate the effect of hypoxic environment stimuli on serum EPO and TfR, possible indirect detection of r-HuEPO use via blood markers of altered erythropoiesis.